Fanny Herself - Ferber, Edna, 1885-1968 (Salt Lake City, UT : Project Gutenberg, 2008)
"Fanny Herself" by Edna Ferber is a novel written in the early 20th century. The story centers around Fanny Brandeis, a young Jewish girl, and her mother, Molly Brandeis, as they navigate life in a small Wisconsin town named Winnebago. The narrative delves into themes of personal growth, gender roles, and the challenges faced by women trying to establish themselves in a male-dominated society. The opening of the book introduces us to the strong character of Molly Brandeis, the owner of Brandeis$1 (BBazaar, who is depicted as an intelligent and determined woman managing her business as a single mother after the death of her husband. The town's dynamics and its characters come alive through vivid descriptions, emphasizing the societal expectations and the pivotal role of mothers in shaping their children's futures. The story hints at the adventurous spirit of Fanny, who is both imaginative and full of energy, while also foreshadowing the challenges she will face as she grows up in a world shaped by tradition and the changing tides of social norms. The mother-daughter relationship, marked by strength and resilience, sets the tone for Fanny's journey into adulthood. (This is an automatically generated summary.)s
Release date is 2008-07-03
Produced by Mike Lough and David Widger
Keywords: Autobiographical fiction; Domestic fiction; Bildungsromans; Mothers and daughters -- Fiction; Jewish fiction; Jewish families -- Fiction; Jewish girls -- Fiction; Wisconsin -- Fiction